THE EFFECT OF GAMIFICATION BASED ON BALINESE LOCAL STORIES AS TEACHING MEDIA TOWARD FIFTH GRADE STUDENTS’ SELF REGULATION IN PRODUCTIVE SKILLS - Putu Agus Eka Lastya Pramana; Putu Kerti Nitiasih; Gd Rahayu Budiarta (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
This research aimed to investigate the effect of Gamification based on Balinese Local Story toward students’ self-regulation in productive skills. The design of this research was one group pretest-posttest. The research population consisted of 150 students of SD Negeri 1 Tukadmungga. Then, the research sample was the 5th-grade students consisted of 20 students. The result shows the writing mean score of the pretest was 0000 and writing mean score of the posttest was 0000. While speaking mean score of the pretest was 0000 and speaking mean score of the posttest was 0000 and the result of the effect size of both writing and speaking was 000 that was the large effect. The result of those analyses showed Gamification based on Balinese local story could improve students’ self-regulation in productive skills. This result also supports by the result of the questionnaire that the motivation of students was increased after implemented gamification in their learning process.